Who is more likely to start a business? Analysis of the factors influencing undergraduates’ entrepreneurial intentions - Li, Yan Yan; Wang, Ruo Xiang; Chi, Chun Yang (Frontiers in Psychology, 2022)
Entrepreneurial intention is an important condition for promoting substantive entrepreneurial behavior, which in turn alleviates employment pressure and promotes sustainable economic and social development. Based on national survey data of university students, descriptive statistical analysis of variables and binary logistic regression analysis were used to empirically analyze the factors influencing university students’ entrepreneurial intentions in five aspects, including innate endowment, acquired characteristics, entrepreneurship courses, and entrepreneurial practice, and social support. The regression results showed that both the factors of innate endowment and acquired characteristics passed the significance test. The entrepreneurship course factor had a significant impact on entrepreneurial intention, with the mean value of the number of entrepreneurship courses hitting 1.80, which is much lower than the other subdivision factors, indicating that there is a greater demand for entrepreneurship courses offered by university students, while the actual situation is less than satisfactory. The entrepreneurial practice factor is also an important factor, with an overall mean of 3 or more, and has a significant impact on entrepreneurial intentions, but in comparison, the factor of having an off-campus practice base for entrepreneurial practice has the lowest mean score, which shows that there is some room for improvement in the construction of off-campus practice bases. The social support factor significantly influences the willingness to start a business, and the mean score for each factor is above the medium level. By understanding which students are more willing to start a business and which factors are more likely to influence their willingness to start a business, we can further consider what kind of entrepreneurial skills and entrepreneurship education can lead to high-quality entrepreneurship and employment.